(3OjhGf GdoeKbH GdYHOjs - (3GdoenKpqbH GdnYrHOj, GdYGFP Hf eMUf Hf KYdHg ef Hfj YHO GdbjS , fMh (B35 (3b g` s ((3eMeO eMehO Hf GdJdGejO GdTfbjWj s)
(3ChdgG (B:s
(3gd YfO ZGmf daDGO nUpO ef fgdI aj Gdjhe Chai ZO s
(3BNQgG (B:s
(3hbGe HUdM Hf Yha, hYGeQ hNWI aUd eG jYGH RYjegG s
(3Vef eLehY , JQJjHgG (B: (3ef U (B80 - (3U(B93s
(3fSNI QGHYIs
(3h gh Vef eLehYI dZhjI HNW GdTfbjWjs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B4s
Keywords: (3GdCOHs